Answer:
Ta fácil le quedan 5 kilos :v de que grado es esto._.
The ticket price that would maximize the total revenue would be $ 23.
Given that a football team charges $ 30 per ticket and averages 20,000 people per game, and each person spend an average of $ 8 on concessions, and for every drop of $ 1 in price, the attendance rises by 800 people, to determine what ticket price should the team charge to maximize total revenue, the following calculation must be performed:
- 20,000 x 30 + 20,000 x 8 = 760,000
- 24,000 x 25 + 24,000 x 8 = 792,000
- 28,000 x 20 + 28,000 x 8 = 784,000
- 26,000 x 22.5 + 26,000 x 8 = 793,000
- 27,200 x 21 + 27,200 x 8 = 788,000
- 26,400 x 22 + 26,400 x 8 = 792,000
- 25,600 x 23 + 25,600 x 8 = 793,600
- 24,800 x 24 + 24,600 x 8 = 792,000
Therefore, the ticket price that would maximize the total revenue would be $ 23.
Learn more in brainly.com/question/7271015
Answer:
B
Step-by-step explanation:
Not all of the pairs represent the same ratio
Answer:
Which unit rate is equivalent to 14 miles per gallon? (1 point
Step-by-step explanation:
i am so glad to hear you are Incredible in messages and please contact us at the free points and see what hi rjha is the most important to you to you amanpreet your support for your support for your child to be a child of your
Answer: x = 0
y = 2
z = -1
Step-by-step explanation:
The system of equations are
x+y+z=1 - - - - - - - - - - 1
-2x+4y+6z=2 - - - - - - - - - 2
-x+3y-5z=11 - - - - - - - - - 3
Step 1
We would eliminate x by adding equation 1 to equation 3. It becomes
4y -4z = 12 - - - - - - - - - 4
Step 2
We would multiply equation 1 by 2. It becomes
2x + 2y + 2z = 2 - - - - - - - - - 5
We would add equation 2 and equation 5. It becomes
6y + 8z = 4 - - - - - - - - - 6
Step 3
We would multiply equation 4 by 6 and equation 6 by 4. It becomes
24y - 24z = 72 - - - - - - - - 7
24y + 32z = 16 - - - - - - - - 8
We would subtract equation 8 from equation 7. It becomes
-56z = 56
z = -56/56 = -1
Substituting z = -1 into 7, it becomes
24y - 24×-1 = 72
24y + 24 = 72
24y = 72 - 24 = 48
y = 48/24 = 2
Substituting y = 2 and z = -1 into equation 1, it becomes
x + 2 - 1 = 1
x = 1 - 1 = 0